Rapping in Catalan in class and the empowerment of the learner. Issue 1 (2nd January 2016) - Aliagas, Cristina; Fernández, Júlia-Alba; Llonch, Pau
ABSTRACT: Despite the well-known educational possibilities afforded by Rhythm And Poetry (RAP) for the development of musical, lyrical and critical skills [Morrell, E., & Duncan-Andrade, J. M. R. (2002). Promoting Academic Literacy with Urban Youth through Engaging Hip-hop Culture. The English Journal, 91(6), 88–92. Retrieved fromhttp://www.jstor.org/stable/821822 ; Hill, M. L. (2009). Beats, Rhymes, and Classroom Life: Hip Hop Pedagogy and the Politics of Identity . New York, NY: Teachers College Press; Low, B. E. (2011). Slam School: Learning Through Conflict in the Hip-Hop and Spoken Word Classroom . Chicago, IL: Stanford University Press], it remains a lyrical genre often excluded from Catalan secondary education. This paper focuses on a four-day series of rap workshops given in 2012 by a famous local Catalan rap artist in a multicultural and multilingual state school in Catalonia. It analyses the impact that the workshops had, above all in terms of classroom engagement, linguistic empowerment and textual 'agency' [Moje, E. B., & Lewis, C. (2007). Examining Opportunities to Learn Literacy: The role of critical sociocultural literacy research. In E. B. Moje, C. Lewis, & P. Enciso (Eds.), Reframing sociocultural research on literacy: identity, agency and power (pp. 15–48). Mahwah, N. J.: Lawrence Erlbaum], on a range of students with varying degrees of command of the Catalan language and with different degrees of experience with rap music. Through the classroom activity described herein, we show the pedagogical opportunities that rap music offers as a hybrid text in-between oral and written codes that makes it a powerful vehicle for self-expression, whilst enabling the acknowledgement of real uses of languages and genres related to the cultural practices of urban students, in the classroom. In particular, we argue that bridging Catalan rap culture to the goals of the school curriculum, especially in highly multilingual and multicultural school contexts, helps to promote the socialisation of the Catalan language in and beyond the school.